A hit on American football : a case study of bottom-up framing through op-ed readers' comments - Bell, Travis R.; Sanderson, Jimmy (London : Human Kinetics, Inc., 2016)
In December 2015, the movie Concussion was released. The film portrayed the story of Dr Bennet Omalu, who is credited with discovering chromic traumatic encephalopathy in the brains of deceased National Football League players. Before the release, on December 7, 2015, Omalu penned an op-ed in The New York Times in which he opined that children should not play tackle football. This research explores 114 reader comments on Omalu's op-ed through the lens of Nisbet's bottom-up framing. Using a mixed-methods approach, the results indicated that participants framed the issue through health and safety, American cultural values, parenting liability, and skepticism. Linguistic analysis revealed that comments contained a negative tone, with women's comments being more negative than men's. The analysis suggests that online news forums function as spaces where public deliberation around the viability of children playing tackle football occurs and illustrates the tensions around risk, sport participation, and health and safety that confront parents as they grapple with the decision to let their children play tackle football.
Originally published in Bell, T. R., & Sanderson, J. (2016). A hit on American Football: A case study of bottom-up framing through op-ed readers' comments. International Journal of Sport Communication, 9(4), 499-518. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Omalu, Bennet I; Football for children -- Public opinion; Brain -- Concussion -- Public opinion